Rancang Bangun Sistem Penyortir Logam Pada Bahan Baku Furniture Berbasis Mikrokontroler dengan Metode Beat Frequency - M. Reza Hidayat (KILAT, 2021)
The development of technology is currently experiencing very rapid progress, so that makes the level of mobility and ways of thinking humans are increasing. All human activities have been helped a lot by automatic devices that can be controlled by a control system. Lots of modern tools were created to advance the industry, one of which in the furniture company is to make machines or tools that function to sort out the metal objects in the raw materials to avoid items that are not in accordance with the standard using the Arduino Uno microcontroller with the Beat method Oscillator frequency is a change in the characteristics of the oscillator on the proximity sensor PR 30 when there is a sensor detecting the presence of metal objects. This metal detector works based on the frequency that has been set when there is an object in the form of metal which is located quite close to the proximity sensor.